A responsabilidade dos sócios e a banalização da desconsideração da personalidade jurídica - Freitas, Eduardo Borges de (Universidade do Vale do Rio dos Sinos, 2015)
The present work is a study on the legal personality of the company and the possibility of the removal of that personality, momentarily, to occur accountability of the shareholders for the obligations assumed and not paid by the company. The legal personality has emerged to protect and encourage entrepreneurship, since the partners have their personal assets protected in case of a failure of the company. Over time, to prevent some abuses and fraud committed by some businessmen, he went to apply the disregard of legal entity doctrine and hold the partners with their personal assets, by debts incurred by the company. Also covered is the confusion that is often made by legal professionals between the disregard of legal entity and the simple attribution of responsibility to the partners, when the occurrence of the second one doesn’t need the occurrence of the first one to be applied. The legal provisions which authorize the allocation of liability to the partners for the debts of the company are analyzed, and the art. 50 of the Civil Code the most comprehensive and capable of use in all areas of law. Further, the crisis that currently crosses for the limitation of liability of the partners is analyzed, because where responsibility is becoming usual and disregard of legal entity is quite banal. Finally, we analyze the articles contained in the New Code of Civil Procedure, which now includes the incident of disregard of legal entity.
Keywords: Personalidade Jurídica; Limitação; Crise; Responsabilidade; Desconsideração; Sociedade; Sócios; Banalização; Legislação; Legal Personality; Limitation; Crisis; Responsibility; Disregard; Society; Partners; Banalization; Legislation